Further insights into the taxonomy of the Silene nocturna species complex (Caryophyllaceae): a systematic survey of the taxa from Sardinia and Corsica - Bacchetta, Gianluigi; Carta, Angelino; Paradis, Guilhan; Piazza, Carole; Peruzzi, Lorenzo (Phytotaxa, 2014)
The taxonomy of Silene nocturna subsp. boullui (putatively endemic to W Corsica) and S. valsecchiae (putatively endemic to E Sardinia) is investigated, by means of morphometric and karyological analyses. Both taxa resulted diploid with 2n = 24 chromosomes. On the basis of morphological results, we confirm the species rank for S. valsecchiae, and consider S. nocturna subsp. boullui as the priority name, at subspecies rank, for S. nocturna subsp. capraria (= S. reflexa).